Acoustic emission characterization of sliding wear under condition of direct and inverse transformations in low-temperature degradation aged Y-TZP and Y-TZP-AL2O3; Friction; Vol. 6, iss. 3 - Savchenko N. L. Nikolay Leonidovich; Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Dmitriev A. I. Andrey Ivanovich; Shilko E. V. Evgeny Viktorovich; Grigorjev A. S. Aleksandr Sergeevich (2018, 2018)
Title screen